Portfolio construction and performance evaluation empirical study in industrial sector in Malaysia from 2007 -2016 / Fadilah Abdul Rahim - Abdul Rahim, Fadilah (2017)
This study conducted to minimize risk from the available set of asset by select an optimal portfolio. Portfolio construction need to be constructed. Sharpe Index Model is used, which is regularly employed to assess the performance of mutual funds and portfolio strategies. This study illustrates an analysis of return of the company as the basis for selection, from 2007 to 2016, of all companies listed at Bursa Saham picked from Industrial sectors. Finally the result will be drawn out on the basis of expected risk and return with the help of Sharpe index model. Portfolio evaluating refers to the evaluation of the performance of the investment portfolio. It is essentially the process of comparing the return earned on a portfolio with the return earned on one or more other portfolio or on a benchmark portfolio. Portfolio performance evaluation essentially comprises of two functions, performance measurement and performance evaluation. Performance measurement is an accounting function which measures the return earned on a portfolio during the holding period or investment period. Performance evaluation, on the other hand, address such issues as whether the performance was superior or inferior, whether the performance was due to skill or luck. The ability of the investor depends upon the absorption of latest developments which occurred in the market.